Method for improving stability of perovskite nanocrystals and application
By calcining the mixture of perovskite nanocrystal precursor and micro/mesporous template at a temperature lower than the collapse temperature of the micro/mesporous template, and using inorganic fluoride solution to form a passivation layer, the problem of structural damage of perovskite nanocrystals in high temperature, high humidity and strong light irradiation environments is solved, and its stability and luminescence performance are significantly improved.
Patent Information
- Application Number
- CN202410023183.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-08
- Publication Date
- 2025-03-04
AI Technical Summary
Existing perovskite nanocrystalline materials are prone to structural damage in high temperature, high humidity and strong light irradiation environments, resulting in a degradation of luminescence performance, and the commonly used cladding structures cannot effectively passivate their surface defects.
By calcining the mixture of perovskite nanocrystal precursor and micro/mesporous template at a temperature below the collapse temperature of the micro/mesporous template, perovskite nanocrystals were generated and treated with an inorganic fluoride solution in the hydrothermal method, the F ions were diffused to the surface of the perovskite nanocrystals to form a passivation layer.
It effectively improves the stability of perovskite nanocrystals, reduces the decrease in luminescence intensity under high temperature and light, and extends its stable luminescence time.
Smart Images

Figure CN119552648A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perovskite nanocrystal preparation, and in particular relates to a method for improving the stability of perovskite nanocrystal and an application thereof. Background Art
[0002] Lead halide compounds with perovskite structure are an emerging semiconductor material, especially the all-inorganic perovskite CsPbX3 (X = Br, Cl, I), which has high fluorescence quantum yield, narrow half-width and adjustable emission wavelength, and has great research and application value in lighting and display devices. However, since lead halide perovskite is an ionic compound with soft lattice characteristics, it is easy to cause structural damage in environments such as high temperature, high humidity, and strong light irradiation, resulting in a decrease in its luminescence performance, which hinders the actual luminescence application of perovskite materials. For example: the lead hydroxide coating layer such as PbOHBr that is spontaneously generated by perovskite nanocrystals in water has good water and oxygen barrier ability, but it will gradually turn yellow when the temperature is higher than 70 degrees, resulting in a significant decrease in the luminescence efficiency of perovskite nanocrystals.
[0003] Encapsulating perovskite nanocrystals in coating materials can effectively enhance their stability. For example, using mesoporous silica, molecular sieves and other materials that are prone to collapse at high temperatures as the coating structure of perovskite nanocrystals can well isolate perovskite from the external environment and ensure that perovskite nanocrystals emit light stably in water or high-humidity air. For example: Chinese patents with publication numbers CN110734758A and CN115772401A all require the micro / mesoporous template (mesoporous silica, molecular sieve) to collapse.
[0004] However, these coating structures usually cannot effectively passivate the surface of perovskite nanocrystals, resulting in a large number of surface defects in perovskite nanocrystals. These defects will cause the fluorescence intensity of perovskite nanocrystals to decrease in high temperature or light environment. Therefore, developing a method to improve the stability of perovskite nanocrystals without collapsing the micro / mesoporous template is a technical problem that needs to be solved urgently. Summary of the invention
[0005] The purpose of the present invention is to provide a method and application for improving the stability of perovskite nanocrystals. To achieve the above purpose, the technical solution adopted by the present invention is:
[0006] A method for improving the stability of perovskite nanocrystals comprises the following steps:
[0007] S1. Preparation of perovskite nanocrystals:
[0008] Mixing a perovskite nanocrystal precursor and a micro / mesoporous template to obtain a mixture; calcining the mixture at a temperature lower than the collapse temperature of the micro / mesoporous template, thereby generating perovskite nanocrystals in the pores of the micro / mesoporous template;
[0009] S2, hydrothermal post-treatment;
[0010] The perovskite nanocrystals obtained in step S1 are dispersed in a high-pressure reaction device filled with an inorganic fluoride solution, and the mixed solution is treated by a hydrothermal method to obtain a perovskite luminescent body.
[0011] By adopting the above technical solution: the calcination temperature of step S1 needs to be lower than the pore collapse temperature of the micro / mesoporous template. The high temperature calcination process can decompose the perovskite precursor and form a perovskite luminescent body in the pores of the micro / mesoporous template, but the calcination temperature will not cause the pores to collapse. Therefore, this coating structure still retains the nanopores of the micro / mesoporous template.
[0012] Step S2, during the hydrothermal treatment of the mixed solution, F ions can diffuse to the surface of the perovskite nanocrystal through the mesoporous channels. The F ions with strong electronegativity can form bonds with unpaired, highly positive metal ions (such as Pb ions, Ba ions, Ca ions, Sr ions, etc.) on the perovskite surface to achieve the effect of blocking and passivating the perovskite surface.
[0013] Further, the perovskite nanocrystal precursor includes a CsPbX3 perovskite structure precursor, where X is at least one of Br, Cl, and I. For example, CsPbBr3, CsPb I3, CsPbBr y I 3-y Perovskite structure.
[0014] Furthermore, the CsPbX3 perovskite nanocrystal precursor is composed of a Cs source precursor, a Pb source precursor and a halogen source precursor;
[0015] Wherein: the Cs source precursor includes one or more of cesium halide and cesium carbonate;
[0016] The Pb source precursor includes one or more of lead halide and lead acetate;
[0017] The halogen source precursor includes one or more of cesium halide, lead halide, zinc halide, potassium halide, sodium halide, lithium halide, ammonia halide, calcium halide, strontium halide, and barium halide.
[0018] Further, the micro / mesoporous template is a microporous material and / or a mesoporous material, specifically a type of micro / mesoporous inorganic material having nano-space pores;
[0019] The microporous material is a microporous molecular sieve, microporous silica, microporous titanium dioxide, microporous alumina, microporous transition metal oxide, microporous sulfide, microporous silicate, microporous aluminate or microporous transition metal nitride;
[0020] The mesoporous material is mesoporous molecular sieve, mesoporous silica, mesoporous titania, mesoporous alumina, mesoporous carbon, mesoporous transition metal oxide, mesoporous sulfide, mesoporous silicate, mesoporous aluminate or mesoporous transition metal nitride.
[0021] Furthermore, the inorganic fluoride solution includes an aqueous solution of NaF, KF, LiF, CsF and a combination thereof.
[0022] Furthermore, the hydrothermal reaction temperature in step S2 is >70° C., and the reaction time is at least 1 hour.
[0023] Preferably, the hydrothermal reaction temperature in step S2 is between 150° C. and 250° C. Under the high temperature and high pressure conditions of the hydrothermal reaction, it is favorable for the bonding of the strongly negatively charged fluoride ions and the strongly positively charged metal ions to occur. For example, the pressure of the hydrothermal reaction is between 1 and 100 MPa.
[0024] Furthermore, the high-pressure reaction device in step S2 is a high-pressure reactor.
[0025] Furthermore, the calcination temperature of the perovskite nanocrystal precursor and the micro / mesoporous template is less than 600° C. to prevent the pore structure of the micro / mesoporous template from collapsing.
[0026] In the process of preparing perovskite luminescent materials, the highest calcination temperature used in the present invention is preferably to ensure that the pores of the micro / mesoporous material will not collapse. However, the collapse temperatures of different micro / mesoporous materials are different, and the collapse temperatures of the same material with different structures are also different, but it can be determined that in order to achieve better results, the calcination temperature must not be higher than the lowest collapse temperature of the material. For example, in the micro / mesoporous material exemplified above, the collapse temperature is as low as 300°C. In practice, generally speaking, 300 to 2000°C can ensure that most of the commonly used micro / mesoporous materials collapse. For example, mesoporous silica collapses at 600°C, mesoporous titanium dioxide begins to collapse at 800°C, and so on.
[0027] In addition, the "calcination under conditions lower than the collapse temperature of the micro / mesoporous template" defined in the present invention should also include the use scenarios of using fluxing agents. For example, the Chinese patent with patent application number ZL202211559323.5 also introduces a mesoporous material collapse agent in an attempt to reduce the collapse temperature of the micro / mesoporous material and achieve size control of the perovskite nanocrystals by avoiding agglomeration. It should be pointed out that even if a fluxing agent or collapse agent is added, the calcination temperature of the present application in the preparation of perovskite nanocrystals still needs to be "calcined under conditions lower than the collapse temperature of the micro / mesoporous template" to retain the existence of the pores.
[0028] A perovskite luminescent body, the perovskite luminescent body is prepared by the above method; the pores of the micro / mesoporous template of the perovskite luminescent body are not closed, and a passivation layer containing F element exists in the luminescent body.
[0029] The beneficial effects of the present invention are mainly reflected in:
[0030] 1. In the present invention, the calcination temperature for preparing perovskite nanocrystals shall not be higher than the collapse temperature of the micro / mesoporous template, and the nanopores need to be retained so that the F ions during the hydrothermal treatment can effectively diffuse into the micro / mesoporous template. For example, when mesoporous silica is used as a template, the calcination temperature is usually less than 600°C to ensure that the nanopore structure of the mesoporous silica does not collapse. The present invention passivates the surface of the perovskite nanocrystals in the micro / mesoporous template with F ions through hydrothermal treatment, which further improves the stability of the perovskite.
[0031] 2. In the hydrothermal treatment stage, the product obtained by high-temperature calcination in step S1 of the first stage is dispersed in a high-pressure reactor filled with an inorganic fluoride solution, and the mixed solution is treated by hydrothermal method. Since the ion diameter of F ions is about 0.26nm, which is much smaller than the nanopores of the mesoporous template (the pore diameter is usually greater than 2nm), F ions can effectively diffuse into the micro / mesoporous template. Since F ions have strong electronegativity, they can bond with unpaired metal ions on the surface of perovskite (such as Pb ions, etc.), thereby blocking and passivating the perovskite surface.
[0032] 3. Since perovskite quantum dots easily react with water, thus reducing the luminescence performance, the field of perovskite luminescence research usually has a technical bias that "water needs to be completely isolated during the perovskite preparation process." The purpose of encapsulating and coating perovskite nanocrystals by calcining and collapsing micro / mesoporous templates is also to improve their ability to block water and oxygen.
[0033] However, the present application goes the other way, and makes use of the fact that the PbOHBr and other lead hydroxide coatings that are spontaneously generated by perovskite nanocrystals in water have good water and oxygen barrier capabilities, but gradually turn yellow when the temperature is higher than 70 degrees. Before the PbOHBr and other lead hydroxide coatings fail, the F ions are given time to effectively diffuse into the micro / mesoporous template. After gradually heating to 70°C using the hydrothermal method, the PbOHBr and other lead hydroxide coatings are destroyed using the high temperature and high pressure environment provided by the high-pressure reaction device. At this time, the F ions that have entered the micro / mesoporous template can immediately form bonds with the unpaired, highly positively charged metal ions (such as Pb ions, Ba ions, Ca ions, Sr ions, etc.) on the perovskite surface, thereby achieving the effect of blocking and passivating the perovskite surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a TEM test image of the perovskite nanocrystal after calcination in step S1 of Example 1;
[0035] Figure 2 This is the EDS spectrum test diagram of the perovskite luminescent body after fluoride hydrothermal treatment in Example 1. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific implementation methods described herein are only used to explain the present invention and are not used to limit the present invention.
[0037] The “perovskite nanocrystals” and “perovskite quantum dots” mentioned in the present invention both refer to CsPbX3 perovskite structures.
[0038] Embodiment 1:
[0039] Step S1: Grind and mix 5 mmol CsBr, 5 mmol PbBr2, and 2 g mesoporous molecular sieve (MCM-41) evenly. Place the mixed powder in a muffle furnace and heat it from room temperature to 450°C, and continue heating at 450°C for 120 minutes, then cool it naturally to room temperature to take out the sample powder (perovskite nanocrystal).
[0040] Step S2: Take 300 mg of the calcined powder and disperse it in 30 ml of KF solution with a KF concentration of 3 mol / L. Place the mixed solution in a 50 ml high-pressure reactor and heat the reactor continuously at 180°C for 10 hours. Then cool it naturally to room temperature and take out the sample powder (perovskite luminescent body).
[0041] Experimental analysis: Take the final product of the above preparation process and test its stability in a high temperature environment of 100°C and a strong blue light irradiation environment (350mW / cm2), see Table 1. After 100 hours of high temperature storage, the luminescence intensity of the powder can maintain 82% of the original intensity; after 100 hours of continuous blue light irradiation, the luminescence intensity of the powder can maintain 75% of the original intensity. In contrast (see comparative example), the powder sample obtained only by high temperature calcination under the same high temperature storage and blue light irradiation conditions after 100 hours, the luminescence intensity dropped to 20% and 33% of the initial intensity. The above results prove that the stability of the perovskite luminescent body can be improved after hydrothermal treatment with KF solution.
[0042] like Figure 1 As shown, TEM tests were performed on the calcined perovskite nanocrystals. The TEM images showed that the pores of the mesoporous template did not collapse.
[0043] like Figure 2 As shown, the energy spectrum of the perovskite luminescent material after fluoride hydrothermal treatment shows that there is a F element passivation layer in the perovskite luminescent material, and the F element content is 10.1%.
[0044] Embodiment 2:
[0045] This example demonstrates that other inorganic fluoride solutions, such as NaF, CsF, and LiF, can also improve the stability of perovskite light emitters during the hydrothermal treatment stage.
[0046] The difference between this embodiment and embodiment 1 is that NaF, CsF and Li F are respectively used in the hydrothermal treatment stage, and the concentration and dosage of these fluoride solutions remain the same as those in embodiment 1.
[0047] Experimental analysis: Take the final product of the above preparation process and test its stability in a high temperature environment of 100°C and a strong blue light irradiation environment (350mW / cm2), as shown in Table 1. For the NaF hydrothermal treatment sample, after 100 hours of high temperature storage, the luminescence intensity of the powder can maintain 85% of the original intensity; after 100 hours of continuous blue light irradiation, the luminescence intensity of the powder can maintain 70% of the original intensity. For the CsF hydrothermal treatment sample, after 100 hours of high temperature storage, the luminescence intensity of the powder can maintain 83% of the original intensity; after 100 hours of continuous blue light irradiation, the luminescence intensity of the powder can maintain 77% of the original intensity. For the Li F hydrothermal treatment sample, after 100 hours of high temperature storage, the luminescence intensity of the powder can maintain 89% of the original intensity; after 100 hours of continuous blue light irradiation, the luminescence intensity of the powder can maintain 71% of the original intensity. As a comparison (see comparative example), the powder sample obtained by high temperature calcination alone has a luminescence intensity of 20% and 33% of the initial intensity after 100 hours under the same high temperature storage and blue light irradiation conditions. The above results prove that the stability of perovskite luminescent materials can be improved after hydrothermal treatment with solutions such as NaF, CsF, and Li F.
[0048] Embodiment 3:
[0049] This example will demonstrate that other mesoporous templates are also suitable for use in the present invention.
[0050] The difference between this embodiment and embodiment 1 is that mesoporous silicon oxide nanoparticles are used as templates in the high-temperature calcination stage. The specific process is as follows:
[0051] Grind and mix 5 mmol CsBr, 5 mmol PbBr2, and 2 g mesoporous silica (about 300 nm in diameter) evenly.
[0052] The mixed powder was placed in a muffle furnace and heated from room temperature to 450°C, and continued to be heated at 450°C for 120 minutes, and then naturally cooled to room temperature to take out the sample powder.
[0053] Take 300 mg of the calcined powder and disperse it in 30 ml of KF solution with a KF concentration of 3 mol / L. Place the mixed solution in a 50 ml high-pressure reactor and heat the reactor continuously at 180°C for 10 hours. Then cool it naturally to room temperature and take out the sample powder.
[0054] Experimental analysis: The final product of the above preparation process was tested for stability in a high temperature environment of 100°C and in an environment of strong blue light irradiation (350mW / cm2), as shown in Table 1. After 100 hours of high temperature storage, the luminous intensity of the powder can maintain 75% of the original intensity; after 100 hours of continuous blue light irradiation, the luminous intensity of the powder can maintain 70% of the original intensity. As a comparison (see comparative example), the powder sample obtained by high temperature calcination alone, under the same high temperature storage and blue light irradiation conditions for 100 hours, the luminous intensity dropped to 51% and 27% of the initial intensity.
[0055] Comparative Example 1:
[0056] Grind and mix 5 mmol CsBr, 5 mmol PbBr2 and 2 g mesoporous molecular sieve (MCM-41) evenly.
[0057] The mixed powder was placed in a muffle furnace and heated from room temperature to 450°C, and continued to be heated at 450°C for 120 minutes, and then naturally cooled to room temperature to take out the sample powder.
[0058] Experimental analysis: The final product of the above preparation process was taken to test its stability in a high temperature environment of 100°C and in an environment of strong blue light irradiation (350mW / cm2), as shown in Table 1. After 100 hours of high temperature storage, the luminous intensity of the powder can maintain 20% of the original intensity; after 100 hours of continuous blue light irradiation, the luminous intensity of the powder can maintain 33% of the original intensity.
[0059] Comparative Example 2:
[0060] Grind and mix 5 mmol CsBr, 5 mmol PbBr2, and 2 g mesoporous silica (about 300 nm in diameter) evenly.
[0061] The mixed powder was placed in a muffle furnace and heated from room temperature to 450°C, and continued to be heated at 450°C for 120 minutes, and then naturally cooled to room temperature to take out the sample powder.
[0062] Experimental analysis: The final product of the above preparation process was taken to test its stability in a high temperature environment of 100°C and in an environment of strong blue light irradiation (350mW / cm2), as shown in Table 1. After 100 hours of high temperature storage, the luminous intensity of the powder can maintain 51% of the original intensity; after 100 hours of continuous blue light irradiation, the luminous intensity of the powder can maintain 27% of the original intensity.
[0063] Comparative Example 3:
[0064] Step S1: Grind and mix 5 mmol CsBr, 5 mmol PbBr2, and 2 g mesoporous molecular sieve (MCM-41) evenly. Place the mixed powder in a muffle furnace and heat it from room temperature to 450°C, and continue heating at 450°C for 120 minutes, then cool it naturally to room temperature to take out the sample powder (perovskite nanocrystal).
[0065] Step S2: 300 mg of the calcined powder was dispersed in 30 ml of KF solution with a KF concentration of 3 mol / L, soaked in water for 10 hours, and then the sample powder was taken out.
[0066] Experimental analysis: The final product of the above preparation process was taken to test its stability in a high temperature environment of 100°C and in an environment of strong blue light irradiation (350mW / cm2), as shown in Table 1. After 100 hours of high temperature storage, the luminous intensity of the powder can maintain 45% of the original intensity; after 100 hours of continuous blue light irradiation, the luminous intensity of the powder can maintain 39% of the original intensity.
[0067] Table 1: Comparison of stability test results of samples from different embodiments (comparative examples)
[0068]
[0069]
[0070] The embodiments described above provide a detailed description of the preparation scheme of the present invention. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for improving the stability of perovskite nanocrystals, characterized in that: The steps include: S1. Preparation of perovskite nanocrystals: Mixing a perovskite nanocrystal precursor and a micro / mesoporous template to obtain a mixture; calcining the mixture at a temperature lower than the collapse temperature of the micro / mesoporous template, thereby generating perovskite nanocrystals in the pores of the micro / mesoporous template; S2, hydrothermal post-treatment; The perovskite nanocrystals obtained in step S1 are dispersed in a high-pressure reaction device filled with an inorganic fluoride solution, and the mixed solution is treated by a hydrothermal method to obtain a perovskite luminescent body.
2. A method for improving the stability of perovskite nanocrystals according to claim 1, characterized in that: The perovskite nanocrystal precursor includes a CsPbX3 perovskite structure precursor, wherein X is at least one of Br, Cl, and I.
3. A method for improving the stability of perovskite nanocrystals according to claim 2, characterized in that: The CsPbX3 perovskite nanocrystal precursor is composed of a Cs source precursor, a Pb source precursor and a halogen source precursor; Wherein: the Cs source precursor includes one or more of cesium halide and cesium carbonate; The Pb source precursor includes one or more of lead halide and lead acetate; The halogen source precursor includes one or more of cesium halide, lead halide, zinc halide, potassium halide, sodium halide, lithium halide, ammonia halide, calcium halide, strontium halide, and barium halide.
4. The method for improving the stability of perovskite nanocrystals according to claim 1, characterized in that: The micro / mesoporous template is a microporous material and / or a mesoporous material.
5. A method for improving the stability of perovskite nanocrystals according to claim 4, characterized in that: The microporous material is a microporous molecular sieve, microporous silica, microporous titanium dioxide, microporous alumina, microporous transition metal oxide, microporous sulfide, microporous silicate, microporous aluminate or microporous transition metal nitride; The mesoporous material is mesoporous molecular sieve, mesoporous silica, mesoporous titania, mesoporous alumina, mesoporous carbon, mesoporous transition metal oxide, mesoporous sulfide, mesoporous silicate, mesoporous aluminate or mesoporous transition metal nitride.
6. The method for improving the stability of perovskite nanocrystals according to claim 1, characterized in that: The inorganic fluoride solution includes an aqueous solution of NaF, KF, LiF, CsF and a combination thereof.
7. The method for improving the stability of perovskite nanocrystals according to claim 1, characterized in that: The hydrothermal reaction condition in step S2 is greater than 70° C. and the reaction time is at least 1 hour.
8. The method for improving the stability of perovskite nanocrystals according to claim 1, characterized in that: The high-pressure reaction device in step S2 is a high-pressure reactor.
9. The method for improving the stability of perovskite nanocrystals according to claim 1, characterized in that: The calcination temperature of the perovskite nanocrystal precursor and the micro / mesoporous template is less than 600° C. to keep the pore structure of the micro / mesoporous template from collapsing.
10. A perovskite light emitting body, characterized in that: The perovskite luminescent body is prepared by the method according to any one of claims 1 to 9; the pores of the micro / mesoporous template of the perovskite luminescent body are not closed, and a passivation layer containing F element exists in the luminescent body.
Citation Information
Patent Citations
Preparation method of semiconductor nanocrystalline fluorescent material, semiconductor nanocrystalline fluorescent material prepared by method and application of semiconductor nanocrystalline fluorescent material
CN110734758A
Perovskite quantum dot and preparation method and application thereof
CN115772401A
Cited By
Perovskite quantum dot with fluorine-containing passivation layer and construction method of fluorine-containing passivation layer
CN119552658A
Perovskite quantum dots with fluorine-containing passivation layer and construction method of fluorine-containing passivation layer thereof
CN119552658B
Method for obtaining small-size perovskite illuminant through post-treatment
CN120590946A
Surface post-treatment process of perovskite quantum dots
CN121628614A
Preparation method of organic-inorganic double-coated rare earth doped perovskite quantum dots
CN121628616A